Economic Openness and Subnational Borrowing. (June 2016) - Liu, Gao; Sun, Rui
Abstract : Using a panel dataset of 206 non‐U.S. subnational governments from 31 countries between 2004 and 2010, this study investigates the relationship between economic openness and sub‐sovereign borrowings. We find that financial openness generates a positive impact on the size of subnational obligations in developing countries but a negative effect in developed countries. It also improves the credit ratings of subnational jurisdictions regardless of the country's development status. However, trade openness does not show any effects on subnational borrowings. To account for these findings that cannot be fully explained by existing theories, we propose a new efficiency hypothesis.